Systematic evaluation and meta-analysis of the efficacy of Jingjin acupuncture therapy in the treatment of peripheral facial palsy - Kang, Xingyu; Huang, Ying; Lv, Xueyan; Liu, Xiaofang; Chen, Siyu; Ma, Le; Shi, Shuai (Frontiers in Neurology, 2024)
ObjectiveThis study aimed to systematically evaluate the clinical efficacy of Jingjin (muscle region of the meridian, sinew/tendon/fascia) acupuncture therapy in treating peripheral facial paralysis.MethodsA computerized search of PubMed, EMBASE, Cochrane Central Register of Controlled Clinical Studies, SCOPUS, Web of Science, PEDro, China Knowledge, Wanfang, and Wipu databases was performed for published randomized controlled trials (RCTs) on the treatment of peripheral facial paralysis using Jingjin acupuncture therapy from the beginning of the construction of the databases until 2 April 2024. After a two-person independent extraction of data, the studies were assessed for paper quality and then analyzed for meta-analysis using RevMan5.4 software.ResultsA total of 19 randomized controlled trials involving 1,436 patients were included. Meta-analysis showed that Jingjin acupuncture therapy for peripheral facial palsy had a higher overall effectiveness rate (OR = 3.93, 95% CI [2.78, 5.56], Z = 7.75, p < 0.00001), and cure rates (RR = 1.69, 95% CI [1.51, 1.90], and Z = 8.89, p < 0.00001) were higher than those of conventional therapy. Jingjin acupuncture therapy was also superior to conventional acupuncture therapy in terms of Facial Disability Index-Physical (FDIP) scores, Facial Disability Index-Social (FDIS) scores, facial nerve function scores, and Portmann scores on the Facial Disability Index Scale in patients with peripheral facial paralysis.ConclusionJingjin acupuncture therapy is effective in treating peripheral facial paralysis and has better overall efficacy than conventional therapy. However, the reliability is limited by the small number of high-quality studies with scientifically rigorous methods and designs, so more large-sample, high-quality, randomized controlled studies are still needed for further validation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, Identifier CRD42024543195.